Exploring a multisectoral and multilevel response to HIV and aids in South Africa - Mahlangu, Brenda Pinky (My University, 2019)
A multisectoral approach (MSA) - which brings together government, civil society, and the private sector to work together towards a common goal - is considered a key strategy to address complex societal problems. Such problems can never be effectively addressed by one sector acting alone, they require integrated efforts of multiple sectors. As such, there has been a widely acknowledged call for a multisectoral approach to respond to development and health issues, including HIV and AIDS. Adoption of MSA promises a number of benefits including cost- and risk- sharing, drawing from the intellect and skill of multiple actors, and the scope to address a problem from varied angels. While highly recommended, implementation of MSA in Southern and Eastern Africa (SEA) has been poor. There has been limited reflection and documentation of experiences of MSA. There are evidence gaps regarding what works and does not work in practice. South Africa’s national response to HIV is premised on MSA, detailed in the National Strategic Plan (NSP) on HIV. This approach centres the role of AIDS Councils, comprised of civil society, government and the private sector, which are meant to coordinate and oversee implementation of a multisectoral response to HIV at all three levels of government (national, provincial and local level). Furthermore, all government departments are expected to mainstream HIV in their work - develop HIV plans detailing how each department plans to address vulnerability and HIV risk internally in the workplace and externally in communities.
Submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy, September 2019
Keywords: HIV infections--Government policy; Government programs